Mechanism of regulating macrophages/osteoclasts in attenuating wear particle-induced aseptic osteolysis - Yin, Zhaoyang; Gong, Ge; Liu, Xinhui; Yin, Jian (Frontiers in Immunology, 2023)
Joint replacement surgery is the most effective treatment for end-stage arthritis. Aseptic loosening caused by periprosthetic osteolysis is a common complication after joint replacement. Inflammation induced by wear particles derived from prosthetic biomaterials is a major cause of osteolysis. We emphasize that bone marrow-derived macrophages and their fusion-derived osteoclasts play a key role in this pathological process. Researchers have developed multiple intervention approaches to regulate macrophage/osteoclast activation. Aiming at wear particleinduced periprosthetic aseptic osteolysis, this review separately discusses the molecular mechanism of regulation of ROS formation and inflammatory response through intervention of macrophage/osteoclast RANKL-MAPKs-NF-κB pathway. These molecular mechanisms regulate osteoclast activation in different ways, but they are not isolated from each other. There is also a lot of crosstalk among the different mechanisms. In addition, other bone and joint diseases related to osteoclast activation are also briefly introduced. Therefore, we discuss these new findings in the context of existing work with a view to developing new strategies for wear particle-associated osteolysis based on the regulation of macrophages/osteoclasts.